Menumbuhkan Jiwa Wirausaha Kalangan Anak Muda Melalui Program Wirausaha Merdeka - Sitti Retno Faridatussalam; Alfian Hikamul Abid; Nazarudin Hasan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The implementation of the independent entrepreneur program is based on the increasing unemployment rate in Indonesia so that the government makes a breakthrough through the independent entrepreneur program with the aim of (a) Providing education to students about the Independent Entrepreneur program, (b) Implementation of the process of Independent Entrepreneur activities, (d) Analysis of the output planning of Independent Entrepreneurs towards society, (e) Development of an entrepreneur-oriented mindset of students. The method used is a combination of leaning by doing and training to produce a marketable product. A total of 5 students accompanied by 1 Field Supervisor (DPL) and 1 Mentor from UMKM. With the independent entrepreneur program, it can produce students who have an entrepreneurial mentality and increase motivation for interest in entrepreneurship.